Patterns, aetiology and risk factors of intimate partner violence-related injuries to head, neck and face in Chinese women - Wong, Janet Yuen-Ha (BioMed Central, 2014)
BACKGROUND: Intimate partner violence (IPV) related injuries have been recognized among health care professionals. However, few studies have provided detailed information on injuries to the head, neck and face regions in Chinese women. As abused Chinese women are generally unwilling to disclose IPV and there are differences in socio-demographic characteristics, societal norms and behaviours, the women may exhibit different patterns, aetiology and risk factors of IPV-related HNF injuries. This study aims to examine the patterns of head, neck and face injuries presenting to Accident and Emergency departments, including the anatomical regions, types, severity, aetiology and demographic and non-demographic risk factors of injuries inflicted by intimate partners in Chinese context. METHODS: Medical charts of 223 women presented to the Accident and Emergency departments of two regional hospitals in Hong Kong between January 2010 and December 2011 were reviewed independently by two reviewers. RESULTS: Head, neck and face injuries remained the most common injuries found in abused Chinese women (77.6%), and punching with a fist was the most common aetiology (60.2%). In particular, punching with a fist was significantly associated on the upper third of the maxillofacial region (p = .01) and the back part of the head (p = .03). Moreover, cohabiting and separated women were more likely to have multiple injuries than those who were married (OR = 3.3, 95% CI = 1.4, 7.8; OR = 2.1, 95% CI = .4, 11.9). CONCLUSIONS: The findings enhance the understanding of head, neck and face injuries and inform clinicians about the linkage among injuries and risks in abused Chinese women.